Pengaruh Kualitas Produk dan Store Atmosphere terhadap Minat Beli Kopi Soe di Harapan Indah, Bekasi - Marchelino Michelin Gunawan; Tinton Ramadhan (UNIVERSITAS KALBIS, 2022)
The expansion of coffee shops is compelling proprietors to seek new strategies for continued success and survival in the face of intensifying competition. This research aims to investigate the connection between Product Quality, Store Atmosphere, and Purchase Intention. This study comprises one independent variable, Buy Intention, and two independent variables, Product Quality and Store Atmosphere. The researchers employed quantitative methods, and the sample comprised 150 respondents with prior knowledge of Kopi Soe.The technique used in this study is simple random sampling. With the results showing that the Product Quality variable significantly influences Purchase Interest, and Store Atmosphere also influences Purchase Interest, and Product Quality and Store Atmosphere together influence consumer Purchase Interest.